2005
DOI: 10.1002/jnr.20501
|View full text |Cite
|
Sign up to set email alerts
|

Pontine‐wave generator activation‐dependent memory processing of avoidance learning involves the dorsal hippocampus in the rat

Abstract: The aim of this study was to test the hypothesis that the dorsal hippocampus plays a critical role in pontine-wave (P-wave) generator activation-dependent memory processing of two-way active avoidance (TWAA) learning. To achieve this objective, rats were given small bilateral lesions in the CA1, dentate gyrus (DG), or CA3 region of the dorsal hippocampus by microinjecting ibotenic acid. After recovery, lesioned and sham-lesioned rats were trained on a TWAA learning paradigm, allowed a 6-hr period of undisturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…2,3 REM-related phasic pontine wave 53 and hippocampal theta activity 54 have been implicated in memory processing rather than REM per se, suggesting that some of the effects of manipulating BLA may be mediated via neural circuitry involved in REM regulation.…”
Section: Bla Involvement In Rem Regulationmentioning
confidence: 99%
“…2,3 REM-related phasic pontine wave 53 and hippocampal theta activity 54 have been implicated in memory processing rather than REM per se, suggesting that some of the effects of manipulating BLA may be mediated via neural circuitry involved in REM regulation.…”
Section: Bla Involvement In Rem Regulationmentioning
confidence: 99%
“…Several studies have demonstrated that lesions in the CA3 subfield prevent retention, but not acquisition, of TWAA memory [10, 6467]. There is increased activation of the immediate and early gene cFos in the CA3 region following both TWAA training and intracranial self-stimulation of the lateral hypothalamus, each of which improved memory retention during TWAA and together their actions had an additive on both CA3 cFos expression and TWAA performance [68].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the dorsal hippocampus has long been considered the site of temporal integration of the sequence of events that ultimately forms a memory, including spatial and contextual learning (reviewed in [10]). Hippocampal neurons play a critical role in the retrieval of information related to memory tasks [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has implicated the pontine waves associated with phasic REM as important for hippocampus-dependent memory consolidation (Datta et al, , 2005Mavanji et al, 2004). Reinstatement of CA3-CA1 communication during phasic bouts of REM sleep may provide windows of opportunity for information encoded in the dentate during tonic REM to be replayed back to the neocortex (Louie and Wilson, 2001).…”
Section: Functional Implications Of Rem/waking Changes In Hippocampalmentioning
confidence: 99%